Endoplasmic Reticulum Stress in Intestinal Epithelial Cell Function and Inflammatory Bowel Disease - Katherine Luo; Stewart Siyan Cao (Gastroenterology Research and Practice)
In eukaryotic cells, perturbation of protein folding homeostasis in the endoplasmic reticulum (ER) causes accumulation of unfolded and misfolded proteins in the ER lumen, which activates intracellular signaling pathways termed the unfolded protein response (UPR). Recent studies have linked ER stress and the UPR to inflammatory bowel disease (IBD). The microenvironment of the ER is affected by a myriad of intestinal luminal molecules, implicating ER stress and the UPR in proper maintenance of intestinal homeostasis. Several intestinal cell populations, including Paneth and goblet cells, require robust ER function for protein folding, maturation, and secretion. Prolonged ER stress and impaired UPR signaling may cause IBD through: (1) induction of intestinal epithelial cell apoptosis, (2) disruption of mucosal barrier function, and (3) induction of the proinflammatory response in the gut. Based on our increased understanding of ER stress in IBD, new pharmacological approaches can be developed to improve intestinal homeostasis by targeting ER protein-folding in the intestinal epithelial cells (IECs).